Panda3D 1.7 game developer's cookbook : over 80 recipes for developing 3D games with Panda3D, a full-scale 3D game engine /: over 80 recipes for developing 3D games with Panda3D, a full-scale 3D game engine. (©2011) - Unknown
No abstract available